Tensile creep properties of a CrMnFeCoNi high-entropy alloy. (15th March 2021) - Zhang, M.; George, E.P.; Gibeling, J.C.
Abstract: Tensile creep tests were performed on a CrMnFeCoNi high-entropy alloy at temperatures from 1023 K to 1173 K. A uniform stress exponent 3.7 ± 0.1 was found across all temperatures. The apparent activation energies of creep under various applied stresses were determined to be around 230 kJ/mol and decrease with increasing stress, indicating a stress-assisted, thermally activated behavior. Steady-state creep microstructures feature no subgrain formation and high dislocation density within grains. Based on our results, the creep rate of CrMnFeCoNi is believed to be controlled by both dislocation-dislocation interactions and dislocation-lattice interactions. Graphical abstract: Image, graphical abstract